Linguistic Diversities in Nepal: A Glimpse of Past and Present - Adhikari, Rishiram (International Research Journal of MMC, 2024)
Nepal is known m as a multilingual nation; however, language policies and statistics of languages spoken in Nepal showed the challenges to maintain linguistic diversities in Nepal. In this context, aim of this study is to outline the language policies of Nepal. Constitutional provisions and arguments of the participants were analyzed with geographical and historical contexts. The study also presents the current population census and highlights the statistics of languages on the basis of mother tongue, second language and ancestor language. Government reports, law and rules related language policies, published between 1950 to 2013 were analyzed with the opinions and perceptions of the participants. Throughout history, the language politics in Nepal has undergone significant shifts and changes due to various political transformations. Current statistics of languages show that it is difficult to preserve minority languages because he numbers of speakers is very low. Except that lack of sufficient resource mobilization on the preservation of minority languages, confusing government policies, socio economic and cultural shift of the respected language community creates problems to sustain minorities language in Nepal. Finding of this study can be apply to formulate the policies and programs related to the preservation and promotion of endangered language because the study analyzes the present linguistic polices and statistics of the language spoken in Nepal.